Comparative Cytotoxic Evaluation of Zygophyllum album Root and Aerial Parts of Different Extracts and Their Biosynthesized Silver Nanoparticles on Lung A549 and Prostate PC-3 Cancer Cell Lines - Reda F. A. Abdelhameed; Mohamed S. Nafie; Dina M. Hal; Ali M. Nasr; Shady A. Swidan; Maged S. Abdel-Kader; Amany K. Ibrahim; Safwat A. Ahmed; Jihan M. Badr; Enas E. Eltamany (MDPI AG, 2022)
The current work demonstrates a comparative study between aerial and root parts of Zygophyllum album L. The total phenolic (TPC) and flavonoid content (TFC), in addition to the antioxidant activity, of the crude extracts were investigated, where the aerial parts revealed a higher value overall. By means of UV-VIS and HPLC, rutin and caffeic acid were detected and then quantified as 5.91 and 0.97 mg/g of the plant extract, respectively. Moreover, the biosynthesis of AgNPs utilizing the crude extract of the arial parts and root of Z. album L. and the phenolic extracts was achieved in an attempt to enhance the cytotoxicity of the different plant extracts. The prepared AgNPs formulations were characterized by TEM and zeta potential measurements, which revealed that all of the formulated AgNPs were of a small particle diameter and were highly stable. The mean hydrodynamic particle size ranged from 67.11 to 80.04 nm, while the zeta potential ranged from 29.1 to 38.6 mV. Upon biosynthesis of the AgNPs using the extracts, the cytotoxicity of the tested samples was improved, so the polyphenolics AgNPs of the aerial parts exhibited a potent cytotoxicity against lung A549 and prostate PC-3 cancer cells with IC50 values of 6.1 and 4.36 µg/mL, respectively, compared with Doxorubicin (IC50 values of 6.19 and 5.13 µg/mL, respectively). Regarding the apoptotic activity, polyphenolics AgNPs of the aerial parts induced apoptotic cell death by 4.2-fold in PC-3 and 4.7-fold in A549 cells compared with the untreated control. The mechanism of apoptosis in both cancerous cells appeared to be via the upregulation proapoptotic genes; p53, Bax, caspase 3, 8, and 9, and the downregulation of antiapoptotic gene, Bcl-2. Hence, this formula may serve as a good source for anticancer agents against PC-3 and A549 cells.